2019
DOI: 10.1371/journal.pgen.1008279
|View full text |Cite
|
Sign up to set email alerts
|

A functional regulatory variant of MYH3 influences muscle fiber-type composition and intramuscular fat content in pigs

Abstract: Muscle development and lipid accumulation in muscle critically affect meat quality of livestock. However, the genetic factors underlying myofiber-type specification and intramuscular fat (IMF) accumulation remain to be elucidated. Using two independent intercrosses between Western commercial breeds and Korean native pigs (KNPs) and a joint linkage-linkage disequilibrium analysis, we identified a 488.1-kb region on porcine chromosome 12 that affects both reddish meat color (a*) and IMF. In this critical region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 66 publications
3
61
2
Order By: Relevance
“…However, the relationship between oxygen consumption and meat quality needs to be further evaluated to understand color variations between the two groups of pigs. A study of the muscle fiber type of Korean native pig reported a higher proportion of type I muscle fibers than that in commercial cross-bred pigs [ 32 ]. The type I slow twitch fiber has a higher mitochondria content for oxidative phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the relationship between oxygen consumption and meat quality needs to be further evaluated to understand color variations between the two groups of pigs. A study of the muscle fiber type of Korean native pig reported a higher proportion of type I muscle fibers than that in commercial cross-bred pigs [ 32 ]. The type I slow twitch fiber has a higher mitochondria content for oxidative phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between muscle fiber composition and IMF content is complex but high correlation was observed. Recent study showed that a functional regulatory sequence variant in porcine MYH3 led to large amount of slow myofibers in the muscles and excess accumulation of IMF (Cho et al, 2019). Slow muscle fiber contains higher lipid than fast muscle fiber.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen consumption also represents the activation of mitochondrial metabolism. A study of the muscle fiber type of Korean native pig reported higher portion of type I muscle fibers than that of the commercial cross-bred pigs [27]. The type I slow twitch fiber has more content of mitochondria for oxidative phosphorylation.…”
Section: Oxygen Consumptionmentioning
confidence: 95%